Performance Investigation of the UTeM Eco-Car Disc Brake System - Khalid, Mohamad Kamal; Mansor, Muhd Ridzuan; Abdul Kudus, Syahibudil Ikhwan; Mohd Tahir, Musthafah; Hassan, Muhammad Zahir (IJENS Publishers, 2011)
The aim of this study is to investigate the braking performance of the UTeM Eco-Car disc brake system. The disc brake system utilized a single cross-drilled rotor with fixed calliper design. The brake system performance in term of its thermal property was determined in transient condition using ABAQUS CAE finite element analysis software. Results from the thermal analysis showed that the maximum temperature generated at the brake disc surface was 119.2 C, which is within the allowable service temperature of the disc material. This indicates that the UTeM Eco-Car disc brake system is able to perform safely as per design requirement.